Kepribadian Atlet: Tinjauan Teoritis Dari Persepektif Psikodinamis - permadi, agung wahyu (Fakultas Ilmu Olahraga, Universitas Negeri Surabaya, 2018)
The purpose of this review is to conduct a review of representative studies of the athlete's personality from the perspective of personality structure, personality dynamics, personality development, personality measurement. The method we did was a literature review of several books and scientific journals on sports psychology. The conclusions from this literature review that psychodynamic perspectives contribute to the development of certain personality traits although the maturity aspect of children and adolescents is also involved in the experience of the athlete itself, in contrast to athletes who already have a personality that can maintain a personality pattern seen in terms of psychodynamic distant more regularly from time to time. Suggestions: There are relevant aspects that we need to improve in future studies, which further determine the formation of the research sample. As noted in this study, the words